The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph191912464
|View full text |Cite
|
Sign up to set email alerts
|

Workforce Experiences of a Rapidly Established SARS-CoV-2 Asymptomatic Testing Service in a Higher Education Setting: A Qualitative Study

Abstract: The aim of the study was to explore workforce experiences of the rapid implementation of a SARS-CoV-2 asymptomatic testing service (ATS) in a higher education setting during the COVID-19 pandemic. The setting was a multi-campus university in the UK, which hosted a testing service for employees and students over two years. Qualitative semi-structured videoconference interviews were conducted. We contacted 58 participants and 25 were interviewed (43% response rate). Data were analysed thematically. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Within the ATS, transformational leadership (e.g., influencing, transforming, and inspiring others), a distributed leadership style (e.g., where teams share responsibility and work towards a common goal) and proactive individual and team behaviour facilitated the implementation of the service. The impact of university investment in employee development through the ATS is evident in our data and interrogated elsewhere [ 49 ].…”
Section: Discussionmentioning
confidence: 67%
“…Within the ATS, transformational leadership (e.g., influencing, transforming, and inspiring others), a distributed leadership style (e.g., where teams share responsibility and work towards a common goal) and proactive individual and team behaviour facilitated the implementation of the service. The impact of university investment in employee development through the ATS is evident in our data and interrogated elsewhere [ 49 ].…”
Section: Discussionmentioning
confidence: 67%
“…Psychological security refers to employees' positive perceptions and judgments that the environment they are in is safe enough (Edmondson, 1999), all of which are footstone steading well-performing individual/teams (Hackman & Hackman, 2002;Blake et al, 2022;Greenbaum et al, 2020). Research has shown that employees who feel psychologically safe are better equipped to handle challenging job demands and this psychological environment has a significant positive impact on their job skills and employability (Plomp, Tims, Khapova, Jansen, & Bakker, 2019).…”
Section: The Mediating Role Of Psychological Securitymentioning
confidence: 99%